Podoplanin emerges as a functionally relevant oral cancer biomarker and therapeutic target. (March 2018) - Retzbach, Edward P.; Sheehan, Stephanie A.; Nevel, Evan M.; Batra, Amber; Phi, Tran; Nguyen, Angels T.P.; Kato, Yukinari; Baredes, Soly; Fatahzadeh, Mahnaz; Shienbaum, Alan J.; Goldberg, Gary S.
Highlights: Oral cancer kills over 100, 000 people worldwide every year. New treatments are needed to more effectively combat oral cancer. Podoplanin (PDPN) can be used as oral cancer biomarker and chemotherapeutic target. Abstract: Oral cancer has become one of the most aggressive types of cancer, killing 140, 000 people worldwide every year. Current treatments for oral cancer include surgery and radiation therapies. These procedures can be very effective; however, they can also drastically decrease the quality of life for survivors. New chemotherapeutic treatments are needed to more effectively combat oral cancer. The transmembrane receptor podoplanin (PDPN) has emerged as a functionally relevant oral cancer biomarker and chemotherapeutic target. PDPN expression promotes tumor cell migration leading to oral cancer invasion and metastasis. Here, we describe the role of PDPN in oral squamous cell carcinoma progression, and how it may be exploited to prevent and treat oral cancer.